THE MODEL OF STATISTICAL CHARACTERISTICS DETERMINATION OF NONLINEAR STOCHASTIC PROCESSES USING MULTIDIMENSIONAL DIFFERENTIAL TRANSFORMATIONS - Oleksandr Y. Permiakov; Serhii V. Kovbasiuk; Ihor D. Varlamov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
Proposed an approach to determine the probability characteristics of vector nonlinear stochastic equations with additional allowance of quadratic terms in the expansion of functions in a Taylor series and calculation of partial derivatives of functions from the input source on the basis of multidimensional differential transformations. Shows the results of simulation on an example of a comparative analysis of extrapolation of space object provisions.